Cryptocurrency in the Turkish Republic of Northern Cyprus: Overview, legal status, and future outlook - Shinda, Frederic Fida; Katircioglu, Setareh (Asian Economic and Financial Review, 2025)
The integration of blockchain technology with cryptographic protocols enables cryptocurrencies to revolutionize global financial systems through decentralized value exchange networks that operate independently of traditional banking institutions. The rapid expansion of these technologies faces challenges such as regulatory uncertainty and a lack of institutional understanding, which hinder their broader adoption. This research investigates the status of cryptocurrencies within the Turkish Republic of Northern Cyprus (TRNC), a distinct political entity with limited financial ties and minimal regulatory oversight. The study employed quantitative methods, collecting data from 210 participants across urban centers, including Kyrenia, Nicosia, and Famagusta. Data analysis was conducted using SPSS software. The research explores residents' understanding of digital currencies, ownership patterns, perceptions of risk, and their desire for regulatory frameworks. Results reveal that residents of TRNC are increasingly engaging with digital currencies; however, concerns persist regarding the absence of legal protections, market volatility, and regulatory gaps. Public participation in cryptocurrency activities outpaces the preparedness of institutional frameworks, highlighting the urgent need for legal development to safeguard investors and foster innovation. Given the TRNC's geopolitical proximity to Türkiye, which is actively advancing blockchain infrastructure, it is likely that the TRNC's policy trajectory will mirror regional trends. This study offers rare empirical insights into cryptocurrency adoption in a politically unrecognized region and underscores the urgency of establishing standardized regulatory measures to foster sustainable growth in the digital currency sector.